Antimicrobial Activities of Laurus nobilis Leaves Ethanol Extract on Staphylococcus aureus, Salmonellae typhi, and Escherichia coli. - Sakran, khawla Abdullah; Raharjo, Dadik; Mertaniasih, Ni Made (Indonesian Journal of Tropical and Infectious Disease, 2021)
Laurus nobilis is one of the most well-known, most frequently used plants is from Lauraceae family which contains up 2.500 species that grow in the subtropics and tropics of the Mediterranean region and Indonesia. This study was supposed to investigate the antimicrobial eï¬€ ect of L.nobilis leaves ethanol extract on Staphylococcus aureus, Salmonellae typhi, and Escherichia coli. This preliminary study examined the antimicrobial eï¬€ ect of L.nobilis leaves ethanol extract. The method used Agar-well diï¬€ usion for determination of the zone of inhibition and the minimum bactericidal concentration to investigate the activity of L.nobilis leaves ethanol extract at 100% concentration . The results revealed that extract of L. nobilis leaves had the antibacterial activity against Staphylococcus aureus with a zone of inhibition (16.3 ±1.5 mm), Staphylococcus aureus with (14.5±0.5 mm), and weak antimicrobial activity against Escherichia coli (11.3±1.1mm). Also, through the minimum bactericidal concentration experiment, the L.nobilis leaves ethanol extract had activity on Staphylococcus aureus and Salmonellae typhi, it's killed the bacteria in all concentration start it from 5í—107 to 5í—104. But the activity on Escherichia coli just weaken concentration 5í—107 and 106. This research has concluded that the L.nobilis leaves ethanol extract exhibited a signiï¬ cant antimicrobial eï¬€ ect against Staphylococcus aureus and Salmonellae typhi then Escherichia coli that is considered a kind of multidrug-resistant bacteria.